Livelihoods and recovery after Cyclone Idai: Short- and long-run household evidence from Mozambique - Allen IV, James; Yu, Hang (International Food Policy Research Institute, 2025)
Sub-Saharan Africa bears a disproportionate share of global poverty and is also among the regions most vulnerable to natural disasters that pose persistent threats to livelihoods, food security, and long-run development. This study examines how exposure to a major natural disaster—Cyclone Idai, one of the deadliest and costliest disasters in Mozambique’s history—affected household well-being and economic behavior in central Mozambique following its landfall in March 2019. We combine satellite-based best-track data on Cyclone Idai’s trajectory with longitudinal household survey data collected both shortly after the disaster and five to six years later. Specifically, we link predicted maximum wind speed at the community level to a pre-defined sample of households surveyed before the cyclone, allowing us to estimate impacts in the short run (within the same year) and the longer run. This design leverages rich pre-baseline data and province fixed effects to mitigate concerns about selection bias, displacement, and omitted variables that commonly complicate causal inference in disaster impact studies.